Beyond interpretation: The meaning of hermeneutics for philosophy - Vattimo, Gianni (Stanford Stanford university press, 1994)
Hermeneutics has had a pervasive influence on contemporary philosophy, social and cultural theory, literary criticism, and aesthetics. It has become so widespread an instrument that its very meaning threatens to dissolve into vague generalities, empty of significance and wedded to a shallow relativism. In this book one of Europes foremost contemporary philosophers provides hermeneutics with a fresh relevance and a substantive account of its philosophical meaning for science, ethics, religion, and art.Vattimo argues for a reading of hermeneutics that radicalizes it according to what the author calls its nihilistic vocation, a term referring to the interpretive character of truth and taken from Nietzsches statement that there are, in the modern period, no facts, only interpretations. Modernity, for Vattimo, is conceived as the advent of nihilism, and the central question of the book is to ask what it means to take this nihilistic vocation seriously. This involves not simply accepting the current status of hermeneutics, but evaluating why it appears when, and where, it does.By way of a response to a number of questions only briefly treated in the text, as well as to broaden the authors argumentation on various points, there is an appendix containing two previously published essays, The Truth of Hermeneutics and The Reconstruction of Rationality.